Political changes in the Amazonia: the PT and the municipal administrations - Chiovetti, Simão Pedro (Pontifícia Universidade Católica de São Paulo, 2004)
The objectives of this article is twofold: a) to examine theprocesses that permitted the appearance and the growth of theLabor Party in a predominantly rural environment, as it the case ofthe State of Rondonia; b) to raise some questions that emergedfrom the analysis of the experience of this party in the municipaladministrations in that region. It is expected that an important facetof the Brazilian political life may be known.